Calculus I - Kelley, W. Michael (Idiot's guides., 2016)
"Let's face it: the thought of Calculus I can be daunting. But it needn't be. in this helpful guide, the fundamentals of Calculus I are taught in easy-to-understand terms, with lots of explanatory graphs and illustrations and over 150 practice problems that feature simple, step-by-step solutions to really explain what you need to know,"--